Performance of the North Sulawesi Province Disaster Management Agency (BPBD) in Flood Management - Tamengkel, Adolf; Dilapanga, Abdul Rahman; Kairupan, Sisca Beatrix (JR Education, 2025)
This study aims to determine the factors that inhibit the performance of the North Sulawesi Provincial BPBD in handling flood disasters in terms of the availability of infrastructure. This study uses a qualitative descriptive method approach, by describing, depicting, or explaining the condition of the object being studied as it is according to the situation and conditions when the research was conducted. Research shows that countermeasures, such as flooding by the BPBD of North Sulawesi Province, have not been optimal due to limitations in the quantity and condition of infrastructure, such as boat rubber and water pumps that are inadequate and already obsolete. Other obstacles include limited budget, slow procurement, and ineffective coordination of inter-agency. Improved equipment and equipment quality, training personnel, and working in the same cross-sector are required to strengthen the response to disaster in a fast and efficient manner in the future.